Penerapan Model Pembelajaran Mastery Learning Untuk Meningkatkan Kemampuan Merumuskan Hipotesis Fisika Siswa Kelas XI SMA Negeri 3 Sibolga - Ferawati Artauli Hasibuan; Henry Dinus Hutabarat (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2019)
This study discusses the improvement of the ability to form physics hypotheses of class XI students of SMA 3 Sibolga through the Mastery Learning model in statistical fluid material. This type of research is a Classroom Action Research (CAR) consisting of 2 cycles. The research subject was class XI IPA 2 which tested 30 people. Learning Tools used in this study are Learning Implementation Plans (RPP), Teacher's Guidebook (BPKS), Student Worksheets (LKS), Test Instruments, Observation Sheets, and activities. While the test used is an essay form test that has been tested with the reliability of the first cycle test of 0.74 with a high level of reliability and the second cycle test of 0.89 with a high level of reliability. And both tests each have 5 valid questions. The results showed that the test results formulated the students' hypotheses by applying the Mastery Learning model in the first cycle obtained a fairly good percentage of 66.67% and in the second cycle increased to 83.32% with the indicators succeeding in getting 80%. Then for the results of observations of activities in the first cycle obtained levels of student activity of 69.63% "Enough" and in the second cycle there was an increase in student activity to 88.63% "Good", Indicators of achieving activities in cycle II also produced 80%.